Intelligent Access Smart Grid System,Metering and Monitoring (International Journal of Engineering and Computer Science, 2017)
A smart grid is an evolved grid system that manages electricity demand in a sustainable, reliable and economic manner, built on advanced infrastructure and tuned to facilitate the integration of all involved. Today existing grids are under pressure to deliver the growing demand for power, as well as electricity. These complex changes are driving the evolution of smart grid technologies. Smart grids make use of materials in system components like transformers and circuit breakers to improve efficiency, safety and operational performance. Widespread use of power electronic devices will help maximize performance of existing asserts and make the grid more resilient in the event of disruptions. More flexible transmission and distribution systems can accommodate fluctuations in supply, increase efficiency and optimize system operations. Powerful monitoring and control system will help prevent disruptions before they occur. A smart grid combines all these features linked by communication technologies. The future electrical system must be able to meet demand for electricity in a way that also satisfies environmental concerns. The biggest changes are in the distribution network and for end users especially commercial and residential users. This report is organized as follows: section II with the prior workwhich is the base for the proposals, section III& IV with the overall work implemented section V contains the simulation result with the comparison.